By the Stream - Hunt, Roderick; Alex brychta (China : Oxford University Press, 2012)
The Stage 3 Biff, Chip and Kipper Stories provide a rich story context to help develop language comprehension and decoding skills. Stories, More Stories A and More Stories B build on the reading skills from Stage 2 and are slightly longer.
Keywords: English-Reading Material